Identifying ‘transit deserts’ in a South African City – The case of Cape Town - Cameron, Robert James (Department of Civil Engineering, 2020)
This dissertation defines and describes the concept of 'transit deserts’, and the important role public transport plays in the lives of people who have few or no other alternatives. Transit deserts are defined as areas containing large portions of public transport dependent populations with limited access to private vehicles where the level of mass public transport does not adequately service the need of the populations in question (Jiao and Dillivan, 2013). The methodology to identify transit deserts (Jiao and Dillivan, 2013; Jiao, 2017) is tested in this study within a South African context, i.e. Cape Town. Since all available literature on measuring transit deserts was generated in the United States, a clearly defined modus operandi was established. Therefore, this dissertation aimed to modify and adapt the existing method to the Cape Town context. An explanation to how certain details related to the existing method were changed to be applicable to a South African city is provided in this study. The modified method involved identifying the public transport dependent population as a measure of public transport need, calculating the supply of public transport, and then measuring the gap between the need and the supply. This study will find that transit deserts exist in Cape Town and are spatially located on the outskirts of the metropolitan, in suburban and rural portions of the city. Transit gaps are also identified in previously marginilised areas known as the Cape Flats. Significantly, this study revealed the need for Cape Town to gather comprehensive transportation network data that is up-to-date and publicly available. This recommendation would allow for a more effective analysis of public transport need and supply in order to report on the location of transit deserts more accurately.